2003
DOI: 10.1097/01.tp.0000052594.83318.68
|View full text |Cite
|
Sign up to set email alerts
|

Predominant expression of Th2 cytokines and interferon-γ in xenogeneic cardiac grafts undergoing acute vascular rejection1

Abstract: Our data demonstrate predominant expression of Th2 cytokines and IFN-gamma in cardiac xenografts undergoing acute vascular rejection. The Th2 cytokines may promote acute vascular rejection by regulating the humoral response, and IFN-gamma may delay, but not prevent, this response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
(23 reference statements)
2
16
0
Order By: Relevance
“…17 Hence, the induction of xenoreactive IL-4 and IL-10 producing splenocytes (Figure 2) and effector T-cells ( Figure 3) were elevated over time and only visible after implantation of free ECs in naïve and presensitized mice. In all mice, cytokine levels correlated linearly and precisely with effector T-cell induction (Figure 4), further supporting the notion of a Th2-driven cellular response in xenoreactivity 15,16 and accentuating the immunosilencing aspects of matrix-embedded ECs to activate adaptive immune mechanisms. This is in line with earlier reports demonstrating different behavior of cells in solution or attached to three-and two-dimensional surfaces.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…17 Hence, the induction of xenoreactive IL-4 and IL-10 producing splenocytes (Figure 2) and effector T-cells ( Figure 3) were elevated over time and only visible after implantation of free ECs in naïve and presensitized mice. In all mice, cytokine levels correlated linearly and precisely with effector T-cell induction (Figure 4), further supporting the notion of a Th2-driven cellular response in xenoreactivity 15,16 and accentuating the immunosilencing aspects of matrix-embedded ECs to activate adaptive immune mechanisms. This is in line with earlier reports demonstrating different behavior of cells in solution or attached to three-and two-dimensional surfaces.…”
Section: Discussionsupporting
confidence: 51%
“…There was no increase in PAE-specific IgG 2a antibodies in the 4 treatment groups (data not shown) supporting previous reports of a dominating T-helper cell 2 (Th2) response in xenografting. 15,16 …”
Section: Matrix-embedding Ecs Prevents Humoral Immune Reactivitymentioning
confidence: 99%
“…In particular, Treg cell development and function are regulated by cytokines, such as IL-2, IL-10, and TGF-␤ (18, 34). We, therefore, characterized the cytokine expression pattern within A20 tumors using RT-PCR with particular focus on Th1 (IL-2, IFN-␥) and Th2/Treg (IL-2, IL-10, TGF-␤) cytokines (26). A20 tumors were found to express low levels of IL-2, IL-4, and IFN-␥; moderate levels of TGF-␤; and high levels of IL-10 (Fig.…”
Section: Intratumoral and Systemic Expression Of Il-10mentioning
confidence: 99%
“…PCR for cytokines and hypoxanthine phosphoribosyltransferase (HPRT) were performed, as previously described (26). PCR for FoxP3 (35 cycles) and IDO (40 cycles) were performed using primers for FoxP3 (forward, 5Ј-CAG CTG CCT ACA GTG CCC CTA G; reverse, 5Ј-CAT TTG CCA GCA GTG GGT AG) and IDO (forward, 5Ј-GAT GTG GGC TTT GCT CTA CC; reverse, 5Ј-TTC TTC CAG TTT GCC AGG AC).…”
Section: Rt-pcrmentioning
confidence: 99%
“…We therefore wished to determine the functional phenotype of the CD4 ϩ T cells that mediate acute corneal xenograft rejection. This is of interest because several studies have reported that Th2 cytokines are expressed predominantly during rejection of xenografts of islets of Langerhans (15)(16)(17)(18), of liver (19), or of concordant heart (20). In this study, we report that Th2 type cytokines are prominently expressed in mouse eyes bearing rejecting guinea pig corneas and in the draining cervical lymph nodes.…”
mentioning
confidence: 70%